2022
DOI: 10.1108/md-03-2022-0345
|View full text |Cite
|
Sign up to set email alerts
|

Involved at work and disinvolved out of work: unraveling the implications of involvement on accountants' work–life balance

Abstract: PurposeBeing involved at work advances accountants' contribution to organizational success. However, scholars are not consistent in discussing involvement's implications on work–life balance (WLB). The article aims to address this issue, investigating involvement's effects on the accountants' ability to manage the work–life interplay.Design/methodology/approachSecondary data on a sample of 538 accountants were collected from the sixth European Working Condition Survey (EWCS). A serial mediation analysis was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 163 publications
2
1
0
Order By: Relevance
“…Matagi et al ( 2022) revealed in their research that job involvement has a significant relationship to job satisfaction. The same results were also obtained by Palumbo (2022) and Roswandi (2021) who also concluded that work/work involvement has a direct and significant effect on job satisfaction. However, research conducted by Salinero et al ( 2020) on 420 employees in Spain showed the opposite result and wrote that there is no significant relationship between job involvement and job satisfaction.…”
Section: Hypotheses Developmentsupporting
confidence: 84%
See 2 more Smart Citations
“…Matagi et al ( 2022) revealed in their research that job involvement has a significant relationship to job satisfaction. The same results were also obtained by Palumbo (2022) and Roswandi (2021) who also concluded that work/work involvement has a direct and significant effect on job satisfaction. However, research conducted by Salinero et al ( 2020) on 420 employees in Spain showed the opposite result and wrote that there is no significant relationship between job involvement and job satisfaction.…”
Section: Hypotheses Developmentsupporting
confidence: 84%
“…This study indicates that most respondents agree that when they have high job involvement in a work, the level of satisfaction they get is also higher. This was also revealed in a study conducted by Matagi et al (2022), Palumbo (2022), Salinero et al (2020 and Roswandi (2021). The positive and significant relationship between job involvement and job satisfaction means that individuals who are highly involved in work generally appear to be satisfied with their jobs.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation